Effectiveness of Information Technology Utilization - Muh. Darwis; Mutmainnah Mutmainnah; Jamaluddin Jamaluddin (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
Information technology allows offices to manage information and communication more effectively and efficiently. By using information technology, offices can optimize the data management process. This study aims to determine the effectiveness of the use of information technology in employees of PT. Midi Utama Indonesia Tbk Makassar, and to find out the supporting and inhibiting factors for the effectiveness of the use of information technology in employees of PT. Midi Utama Indonesia TBk Makassar.  This research uses a qualitative method, therefore in order to achieve a research objective, data collection techniques are used, namely observation, interviews, and documentation. The informants of this research were 5 employees of PT. Midi Utama Indonesia Tbk Makassar. The results of this study show that the effectiveness of the use of information technology in employees of PT. Midi Utama Indonesia Tbk Makassar can be seen from the indicators that hardware, software and brainware are "effective". It can be seen from the aspect that the hardware that uses a computer is adequate with good quality so that it is very helpful for employees in supporting office activities. From the aspect of software used to process data, including processing, compiling, and storing data, it is quite flexible in supporting the work in the office, one of the applications used is a spreadsheet data processing application that produces relevant, accurate and timely information. From the human aspect (brainware) of human resources in the office of PT. Midi Utama Indonesia Tbk Makassar stated that the technology component is very important in carrying out the development of the use of information technology and all the devices that have been provided. The supporting factors of information technology are information systems that utilize information technology to facilitate the management of various forms of facilities and infrastructure as well as information technology that makes it easier for employees to carry out their individual needs, while the factors that hinder the use of information technology are several problems that are often faced including high dependence on information technology, incompatibility with business processes, regulatory readiness,  procedures, and limitations of human resources, information technology is often not supported by an effective management system and work process, as well as limited human resources.